A rare and unusual retinal arterioarterial communication in a prepapillary vascular loop - Makino, Shinji (Massachusetts Eye and Ear Infirmary, 2014)
Fundus examination of a 40-year-old man presenting with blurred vision in his right eye revealed mild vitreous hemorrhage, a prepapillary vascular loop, and a peripapillary epiretinal membrane. Additionally, a superotemporal branch retinal artery communicated directly with an inferotemporal branch retinal artery in the temporal fovea at 2 locations. Fluorescein angiography confirmed an extremely rare arterioarterial communication. Two weeks later the vitreous hemorrhage and small intraretinal hemorrhage had disappeared, and the visual acuity in the right eye improved.